Management of Acute-on-Chronic Kidney Injury in a Golden Retriever - Sachin Manoj; M. Chandrasekar; Balangagatharathilagar M; P Raja; S. Kavitha (Indian Journal of Veterinary Medicine, 2025)
A four-year-old Golden Retriever bitch weighing 26 Kg was presented with the history of inappetence for one week. Clinical examination revealed emaciated, pyrexia, pale mucus membrane, hypertension (170 mmHg). splenomegaly and generalized lymphadenopathy. Laboratory evaluation showed hypochromic anemia with thrombocytopenia, hyposthenuria with proteinuria with elevated blood urea nitrogen and creatinine levels. Nephrosonogram revealed normal parenchyma with good corticomedullary differentiation, with irregular border and increased cortical echogenicity. Polymerase chain reaction (PCR) confirmed Babesia gibsoni infection.. Targeted antiprotozoal therapy comprised a 28-day course of triple antibiotic protocol with doxycycline, clindamycin, and metronidazole along with hematinic and thrombopoietic support. Therapeutic management included fluid therapy, antiemetics, proton pump inhibitors, antihypertensives, phosphate binders, renal-specific diet, and supportive care Marked clinical improvement was observed during follow-up, with progressive normalization of renal parameters, restoration of appetite, and improvement in body condition score.